The effectiveness of using self-adjusting files (SAF) through the results of laboratory research (LLC "Endo Press", 2020)
A primary aim of root canal treatment is to completely clean and shape the root canal system. Various instruments are available for endodontic instrumentation. Although rotary systems do prepare many canals without major procedural errors, they do not address canal types with long-oval or flat cross sections. A newly developed self-adjusting file (SAF) was designed to address the shortcomings of traditional rotary files by adjusting itself to the canal cross section. Latest research with microcomputer tomography demonstrates that the affected area of a root canal operated through SAF shows that majority of the area was operated with the help of a popular nickel-titanium rotary system.